2014
DOI: 10.1160/th13-08-0706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the 9p21.3 CAD risk locus in Asian Indians

Abstract: The 9p21.3 locus is the best replicated region to date for coronary artery disease (CAD). We investigated the association of 9p21.3 common variants with CAD, candidate gene expression including ANRIL, a non-coding RNA, followed by in vitro validation. Five variants, rs10757278, rs10757274, rs2383206, rs1333049 and rs4977574 were genotyped in 1,034 cases and 1,034 controls. Gene expression of C9orf5, MTAP1, MTAP 2, p16INK4a, p14ARF, p15INK4b and two ANRIL splice variants, NR_003529 and EU741058, were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Interestingly the genetic associations seem independent of obesity (Broadbent et al, 2008). Disease associated genotype is also associated with ANRIL expression levels, and ANRIL expression also differs relative to disease (Zhao et al, 2015, Shanker et al, 2014, Bochenek et al, 2013). Previously Zhuang et al (2012) found that methylation in blood at a locus overlapping with the DMR discussed here, was higher in coronary artery disease compared to controls but methylation was not associated with genotype at rs10757274 (Zhuang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the genetic associations seem independent of obesity (Broadbent et al, 2008). Disease associated genotype is also associated with ANRIL expression levels, and ANRIL expression also differs relative to disease (Zhao et al, 2015, Shanker et al, 2014, Bochenek et al, 2013). Previously Zhuang et al (2012) found that methylation in blood at a locus overlapping with the DMR discussed here, was higher in coronary artery disease compared to controls but methylation was not associated with genotype at rs10757274 (Zhuang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Association of three most frequently detected SNP, rs1333049, rs2383206 and rs10757278, in European populations was confirmed in a large meta-analysis of an East Asian population [126]. Among these variants, rs2383206 and rs10757278 displayed the closest association with CAD in an Indian population [127,128]. Investigation of CAD in a Saudi population identified four SNPs including rs564398, rs4977574, rs2891168, and rs1333042 associated with CAD/MI [129].…”
Section: Discussionmentioning
confidence: 82%
“…However, investigation of the rs10757274 and rs1333042 variants showed that the risk alleles of these SNP in a haplotype form did constitute a risk factor for CAD [137]. This demonstrated that some haplotype arrangements have protective effects against CAD, such as a GAAAA haplotype for five common variants, rs1333049, rs10757278, rs2383206, rs4977574 and rs10757274 [127]. The majority of SNP in the ANRIL gene were located in intronic regions, but recently two exonic variants were reported to be associated with MI.…”
Section: Discussionmentioning
confidence: 99%
“…Their study indicated the importance of this SNP due to its involvement in the expression of the EU741058 and p16INK4a genes, modulating the chances of CAD. The same SNP also showed its association with peripheral artery disease in a Han Chinese population (40). These findings are in agreement with our results, obtained without the consideration of covariates.…”
Section: Discussionmentioning
confidence: 86%
“…The family history was associated with the extent and severity of coronary atherosclerotic plaque formation in premature CAD (38). The effects of rs10757274 were investigated by Shanker et al (40). Their study indicated the importance of this SNP due to its involvement in the expression of the EU741058 and p16INK4a genes, modulating the chances of CAD.…”
Section: Discussionmentioning
confidence: 99%